Analisa pengaruh consumption value dan pricing terhadap purchase intention pada pembelian virtual item pada game online - Agustin, Isnaini Nuzula; Samuel, Yang Songsen (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
In the background of the increasingly widespread game online in all circles, this study aims to determine the effect of consumption value to purchase intention on purchasing virtual items online. This study used a purposive sampling method for distributing questionnaires, obtaining a total of 300 respondents who are online game players. The data analysis method used is Partial Least Square Structural Equation Modeling (PLS-SEM). The study results show that Social Value, Good Price, Scarcity, and satisfaction have a significant effect on Purchase Intention. These results also confirm the role of satisfaction as a mediation between Social Value, Good Price, and Scarcity to Purchase Intention. This study is expected to be able to contribute to online game managers in their efforts to increase sales of virtual items through analysis of consumer behavior.